"Leaving the placenta in situ approach" (LISA) in a patient with placenta increta leading to delayed spontaneous delivery of the placenta. (17th January 2020) - Boekhoff, Jelena; Arabin, Birgit; Figiel, Jens; Köhler, Siegmund
Abstract: Aim: Based on the recent FIGO recommendations, we wish to report on preservation of the uterus in a patient with placenta increta by applying the leaving the placenta in situ approach. Methods: A 30-year-old gravida 2, Para 1 was referred at 25 + 5 gestational weeks due to a placenta previa bipartita increta diagnosed by transvaginal ultrasound, a history of a cesarean and vaginal bleeding. After informed consent, the parents opted for conservative treatment. The patient was admitted and the options of treatment were communicated within a multidisciplinary team. At 31 + 4 gestational weeks, severe recurrent hemorrhage led to a repeat cesarean. Results: A boy of 1910 g was delivered and the placenta was left in situ . Estimated blood loss was <200 ml. An MRI on day 13 still showed regular placental circulation, but after 4 weeks, perfusion and HCG levels had significantly decreased. The patient was examined every 3 days and readmitted after 6 weeks with a sudden rise of d -dimers. Within 24 hours, the complete placenta was delivered. On postoperative day 54, MRI confirmed uterine involution without a placental tissue. Conclusions: Delayed placental delivery in patients with abnormal placental invasion is a legitimate option to preserve fertility and possibly to reduce intrapartum hemorrhage.